Przejmowanie kościelnych placówek służby zdrowia oraz zakładów opieki społecznej w archidiecezji wrocławskiej w latach 1945–1956 - Włodarczyk, Edyta (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The article examines the take-over of the Church’s healthcare centres and nursing homes in 1945– 1956, a process based on the Act of 28 October 1948 on healthcare centres, nursing homes and planned economy in health service. Repressions against Church institutions, leading to a conflict between the state and the Church, stemmed from the ideology based on the Marxist doctrine seeking to make society atheist as a prerequisite to carry out profound social reforms. The practice inevitably exacerbated the conflict with the Church in almost all areas of society’s life, including health service. The year 1949 was a time in which the conflict between the state and the Church over health service reached an unprecedented scale. The communist authorities knew that the Church’s influence was at its most extensive in nurse training and hospitals, and believed that the only and the best solution was to introduce organisational and administrative measures facilitating political offensive and limiting the clergy’s material and organisational base. The strongest measure aimed at completely eliminating religious orders from health service institutions was the nationalisation or take-over of hospitals by the state
Keywords: health service; nationalisation of hospitals; Archdiocese of Wrocław; nursing homes; Catholic Church; nuns